A matter of collection and detection for intraoperative and noninvasive near‐infrared fluorescence molecular imaging: To see or not to see?. Issue 2 (23rd January 2014) - Zhu, Banghe; Rasmussen, John C.; Sevick‐Muraca, Eva M.
Abstract : Purpose: : Although fluorescence molecular imaging is rapidly evolving as a new combinational drug/device technology platform for molecularly guided surgery and noninvasive imaging, there remains no performance standards for efficient translation of "first‐in‐humans" fluorescent imaging agents using these devices. Methods: : The authors employed a stable, solid phantom designed to exaggerate the confounding effects of tissue light scattering and to mimic low concentrations (nM–pM) of near‐infrared fluorescent dyes expected clinically for molecular imaging in order to evaluate and compare the commonly used charge coupled device (CCD) camera systems employed in preclinical studies and in human investigational studies. Results: : The results show that intensified CCD systems offer greater contrast with larger signal‐to‐noise ratios in comparison to their unintensified CCD systems operated at clinically reasonable, subsecond acquisition times. Conclusions: : Camera imaging performance could impact the success of future "first‐in‐humans" near‐infrared fluorescence imaging agent studies.